Molecular Phylogeny and Dating of Forsythieae (Oleaceae) Provide Insight into the Miocene History of Eurasian Temperate Shrubs - Ha, Young-Ho; Kim, Changkyun; Choi, Kyung; Kim, Joo-Hwan (Frontiers in Plant Science, 2018)
Tribe Forsythieae (Oleaceae), containing two genera (Abeliophyllum and Forsythia) and 13 species, is economically important plants used as ornamentals and in traditional medicine. This tribe species occur primarily in mountainous regions of Eurasia with the highest species diversity in East Asia. Here, we examine 11 complete chloroplast genome and nuclear cycloidea2 (cyc2) DNA sequences of 10 Forsythia species and Abeliophyllum distichum using Illumina platform to provide the phylogeny and biogeographic history of the tribe. The chloroplast genomes of the 11 Forsythieae species are highly conserved, except for a deletion of about 400 bp in the accD–psaI region detected only in Abeliophyllum. Within Forsythieae species, analysis of repetitive sequences revealed a total of 51 repeats comprising 26 forward repeats, 22 palindromic repeats, and 3 reverse repeats. Of those, 19 repeats were common and 32 were unique to one or more Forsythieae species. Our phylogenetic analyses supported the monophyly of Forsythia and its sister group is Abeliophyllum using the concatenated dataset of 78 chloroplast genes. Within Forsythia, F. likiangensis and F. giraldiana were basal lineages followed by F. europaea; the three species are characterized by minutely serrate or entire leaf margins. The remaining species, which are distributed in East Asia, formed two major clades. One clade included F. ovata, F. velutina, and F. japonica; they are morphologically supported by broadly ovate leaves. Another clade of F. suspensa, F. saxatilis, F. viridissima, and F. koreana characterized by lanceolate leaves (except F. suspensa which have broad ovate leaves). Although cyc2 phylogeny is largely congruent to chloroplast genome phylogeny, we find the discordance between two phylogenies in the position of F. ovata suggesting that introgression of the chloroplast genome from one species into the nuclear background of another by interspecific hybridization in East Asian Forsythia species. Molecular dating and biogeographic reconstructions suggest an origin of the Forsythieae species in East China in the Miocene. Distribution patterns in Forsythia indicated that the species were radially differentiated from East China, and the speciation of the European F. europaea was the result of both vicariance and dispersal in the late Miocene to Pliocene.